Strategi Guru dalam Menumbuhkan Minat Membaca pada Anak Usia Dini Melalui Sudut Baca Kreatif - Rini Melati (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
The development of reading interest in early childhood plays a crucial role in shaping cognitive and language abilities. This research aims to explore teacher strategies in fostering reading interest among young children through the implementation of creative reading corners. This qualitative descriptive study was conducted in a kindergarten setting using observation, interviews, and documentation techniques. The findings show that teachers utilize various strategies such as thematic storytelling, interactive reading sessions, and personalized reading spaces to attract children's attention. The creative reading corner is designed with colorful visuals, age-appropriate books, and engaging media to stimulate curiosity. These efforts significantly contribute to increasing children’s enthusiasm for reading and enhancing their literacy skills. The implication of this study highlights the importance of teacher innovation in designing stimulating reading environments to develop lifelong reading habits from an early age.